ChemInform Abstract: Intramolecular Aminoboration of Unfunctionalized Olefins. Issue 10 (February 2016) - Yang, Chun‐Hua; Zhang, Yu‐Shi; Fan, Wen‐Wen; Liu, Gong‐Qing; Li, Yue‐Ming
Abstract: Intramolecular aminoborylation of sulfonamide substrates by reaction with BCl3 provides boronic acids, which are directly converted into the corresponding boronates.